Analisis Metode Pembelajaran Pendidikan Pada Era Awal dan Pertengahan Islam - Putri, Atik Hidayati (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Education is an important tool that has a big influence on human life, because with education humans can know and overcome the problems that exist in their lives, not only that, Islam also positions education in a very important and high position. We can know the importance of education for humans from history. Islamic education began to develop since the time of the Prophet, the time of Khulafaur Rasyidin, the Ummayah period and the Abbasid period, which is called the early or classical period. And continued with the Middle Ages, where the periodization of Islamic history refers to the existence of three great empires, namely the Ottoman empire in Turkey, the Safavid empire in Persia and the Mughal empire in India. In an education where there is a learning process, of course a method is needed. Method is a method or path that must be followed to achieve educational goals. In the classical/early to middle period, learning methods in education certainly changed according to the situations and conditions experienced at that time.